Twin anaemia-polycythaemia sequence or twin-to-twin transfusion syndrome? How to distinguish postnatally? A case report - Perez, Ewa Rojas; Kłosowska-Kwapisz, Magdalena; Źródłowska, Paula; Fiedorowicz-Kaźmierczak, Marta; Malinowski, Witold (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Twin pregnancy, especially monochorionic, is known to be a high-risk pregnancy, with a high morbidity and mortality rate. Complications that can occur in this type of twins are: twin-to-twin transfusion syndrome, twin anaemia-polycythaemia sequence, twin reversed arterial perfusion, or selective intrauterine growth restriction. Twin-to-twin transfusion syndrome is the most common complication and can affect 10–15% of monochorionic twins. Twin anaemia-polycythaemia sequence is rarer and can be seen in 1–5% of this type of twin pregnancy. Sometimes it is very difficult to differentiate between these two syndromes because some symptoms can overlap. We present a case of monochorionic diamniotic twin pregnancy with an unremarkable course of pregnancy, which was ended prematurely at 33 weeks of gestation due to the onset of labour, complicated by twin anaemia-polycythaemia sequence diagnosed postnatally with a haemoglobin difference of nearly 20 g/dl.